Classified metabolic power-based measures in professional football players: comparison between playing positions and match period - Akyildiz, Z.; Çene, E.; Parim, C.; Çetin, O.; Turan, Ç.; Yüksel, Y.; Silva, R.; Silva, A. F.; Nobari, H. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Objective The aim of this study was (i) provide reference data of metabolic power-based measures during professional football matches; and to (ii) analyze the between-position and between-halves differences of power-based measures during professional football matches.